PEMAKNAAN KHALAYAK DAN HEGEMONI MEDIA MENGENAI NASIONALISME DALAM IKLAN (Studi Resepsi pada Iklan Djarum versi Bull Race, Telkomsel versi Halmahera dan You C1000 versi Miss Universe) - Artyasto Jatisidi (Fakultas Komunikasi & Desain Kreatif - Universitas Budi Luhur, 2016)
The era of globalization took effect on today's Indonesian nationalism, nationalism of the Indonesian nation is distorted away from its original meaning. The symbols of global cultural products as if drowning sense of all Indonesia's youth. On the other hand the mass media also play a role in this, by creating false consciousness and false about the value of nationalism. One is through advertisements on television. The theory used in this research is the Reception Analysis Stuart Hall that positioned the audience at the 3 position, Dominant-hegemonic-hegemonic, Negotiation and Opposition. From the results of these positions are expected to be concluded as to what nationalism typical community-owned Indonesia, and the power of the media hegemony. This study used qualitative methods, with a critical paradigm. Then, the data obtained through interviews with the four informants were selected by purposive sampling. The results showed that the people of Indonesia occupies a tendency on the Negotiation position, they are similar to interpret the ad makers, but they also have alternatives meaning. From the research it can be said that the people of Indonesia has a typical pragmatic nationalism that sees nationalism in terms of togetherness.